Socioeconomic Dimensions of Food Price Fluctuations and Regional Inflation in Indonesia: Insights from Java and Sumatra - Wirda Zahra Siregar; Rulianda Purnomo Wibowo; Elisabet Siahaan (Baileo: Jurnal Sosial Humaniora, 2026)
This study investigates the socioeconomic dynamics of food price volatility and its asymmetric impacts on regional inflation across Java and Sumatra, Indonesia’s two most economically influential islands. The research aims to analyze the short- and long-term effects of food commodity price fluctuations on regional inflation, compare the structure and magnitude of price transmission mechanisms between the two regions, and identify key commodities that drive inflation disparities. Using a quantitative explanatory approach integrated with sociological interpretation, monthly time-series data from 2020 to 2024 across six provinces are analyzed through ADF stationarity tests, VAR/VECM models, Granger causality, impulse response functions, and variance decomposition, complemented by sociological indicators such as logistics index, GRDP per capita, and household food expenditure ratio. The findings show that short-term inflationary pressures stem mainly from price shocks in red chili, shallots, and cooking oil, while long-term persistence is driven by dependence on rice, beef, and chili. Inflation in Java is largely demand-driven, whereas Sumatra’s inflation reflects supply-side constraints and weak market integration. The study’s novelty lies in combining macroeconomic modeling with regional sociological analysis, offering a socioeconomic inflation dynamics framework that reframes inflation as a socially embedded process. The research advances economic sociology by linking inflation behavior with social structure, regional inequality, and policy responsiveness.